Empire and New Testament texts: Theorising the imperial, in subversion and attraction - Punt, J. (HTS teologiese studies, 2012)
Considering the overt or sublime connections biblical scholars increasingly indicate between biblical texts and empires, this contribution engages the need for the theorisation of empire beyond material depiction. It is suggested that empire is primarily of conceptual nature and a negotiated notion, a constantly constructed entity by both the powerful and the subjugated, to which the concomitant responses of subversion and attraction to empire attest. The discussion is primarily related to the first-century CE context, arguing also that postcolonial analysis provides a useful approach to deal with (at least, some of) the complexities of such research.